2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00506
|View full text |Cite
|
Sign up to set email alerts
|

Binary Ensemble Neural Network: More Bits per Network or More Networks per Bit?

Abstract: Binary neural networks (BNN) have been studied extensively since they run dramatically faster at lower memory and power consumption than floating-point networks, thanks to the efficiency of bit operations. However, contemporary BNNs whose weights and activations are both single bits suffer from severe accuracy degradation. To understand why, we investigate the representation ability, speed and bias/variance of BNNs through extensive experiments. We conclude that the error of BNNs are predominantly caused by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 50 publications
0
83
0
Order By: Relevance
“…cial characteristics of BNNs are necessary. In fact, some of the recent works essentially worked on this such as XNOR-Net++[76], CBCN[88], Self-Binarizing Networks[94], BENN[67], etc. The results show that specially designed methods considering characteristics of BNNs can achieve better performance.…”
mentioning
confidence: 99%
“…cial characteristics of BNNs are necessary. In fact, some of the recent works essentially worked on this such as XNOR-Net++[76], CBCN[88], Self-Binarizing Networks[94], BENN[67], etc. The results show that specially designed methods considering characteristics of BNNs can achieve better performance.…”
mentioning
confidence: 99%
“…For all the three benchmarks, additional experiments revealed the accuracy of TentacleNet saturates, namely, there is no further improvement by increasing the number of tentacles; the top right points of the three lines in the plot of Fig. 3 a quantitative comparison against BENN [16], which is state-of-the-art for binary ensembles. The BENN strategy is to apply standard ensemble methods to BNNs, bagging and boosting in particular.…”
Section: Performance Assessmentmentioning
confidence: 99%
“…Some recent works explored this option. For instance, in [16] the authors adapted the classical ensemble methods to binary CNNs, bagging and boosting in particular. The collected results revealed that a large number of BNNs is needed to get close to the accuracy of the full-precision model, thus resulting in large memory space.…”
Section: Ensembles Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…For the CIFAR-10 dataset, for example, binary networks such as FINN and ReBNet require a wider and deeper model, CNV, in order to achieve similar accuracy to an FP32 baseline with CifarNet, a much thinner and shallower model [130]. Zhu et al proposed the Binary Ensemble Neural Network (BENN), in which multiple binarised networks are aggregated by "boosting" (parallel ensemble with trained weights) [163]. e authors showed that their network ensembles exhibited lower bias and variance than their individual constituents while also having improved robustness to noise.…”
Section: Binarisation and Ternarisationmentioning
confidence: 99%